Foreign Object Insertions in Sexual Homicide - Koeppel, Sydney (International journal of offender therapy and comparative criminology, 2019)
A nonrandom national sample of 260 sexual homicides (207 nonserial and 53 serial) disclosed 50 cases in which an offender (45 nonserial and 10 serial) inserted a foreign object into a victim's orifice. The prevalence of foreign object insertion, as well as the types and shapes of inserted objects, where the objects were obtained, the bodily location of insertions, the visibility of inserted objects at the scene, and whether the insertions were pre- or post-mortem are all reported. The foreign object insertion prevalence rate for the sexual homicide sample of cases is 19.2%. Nonserial offenders engaged in foreign object insertion at about the same rate (21.7%) as the serial offenders (18.8%). Our findings do not support the largely held notions—based mainly on case reports—that most offenders who engage in foreign object insertion are psychotic and that the insertion behavior is always post-mortem. The insertion behavior of the nonserial offenders reflects a level of sadism and deviancy comparable with the serial offenders, an unexpected finding with possible prognostic implications.